Efeitos do exercício físico na função muscular do joelho, dor e qualidade de vida em mulheres pós-menopausadas com osteoartrite de joelho: uma revisão sistemática com metanálise - Wolf, Débora Faria (2023)
Objective: To investigate the effects of physical exercise on muscle function of the knee, pain and quality of life in postmenopausal women with knee osteoarthritis (OA). Methods: An electronic search was conducted of the PubMed, Embase, Web of Science, Cochrane Library, LILACS and PEDro databases for relevant articles published up to February 2023. Only randomized clinical trials with interventions involving physical exercise of any modality in postmenopausal women with knee OA were included. This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and the Cochrane Recommendations. Methodological quality of the studies selected was assessed using the PEDro scale and the evidence was synthesized using the Grading of Recommendations, Assessment, Development and Evaluation scale. Results: Among the 146 articles identified, five were included in the present systematic review and enabled meta-analysis of the outcomes physical function, pain and stiffness. Treatment with physical exercise proved effective at improving physical function compared to the control based on the distance traveled on the Six-Minute Walk Test. However, no difference was found when assessed based on self-reports. No differences between the treatment and control groups were found for the outcomes pain or stiffness. Meta-analysis was not possible for the outcomes muscle function of the knee or quality of life due to insufficient data. Conclusion: Physical exercises can contribute to the improvement in physical function in postmenopausal women with knee OA when assessed by the distance travelled, but not by the self-report assessment